2021
DOI: 10.2478/popets-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Vax: Studying User Preferences and Perception of Covid Vaccination Certificates

Abstract: Digital tools play an important role in fighting the current global COVID-19 pandemic. We conducted a representative online study in Germany on a sample of 599 participants to evaluate the user perception of vaccination certificates. We investigated five different variants of vaccination certificates based on deployed and planned designs in a between-group design, including paper-based and app-based variants. Our main results show that the willingness to use and adopt vaccination certificates is generally high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Given that population-based research regarding these app functionalities is scarce [ 29 , 30 ], we investigated how users and nonusers differ in their attitudes toward these potential features. For instance, the app could indicate that its holder did not have close contact with another user who tested positive for COVID-19, in order to gain access to public places or other locations.…”
Section: Introductionmentioning
confidence: 99%
“…Given that population-based research regarding these app functionalities is scarce [ 29 , 30 ], we investigated how users and nonusers differ in their attitudes toward these potential features. For instance, the app could indicate that its holder did not have close contact with another user who tested positive for COVID-19, in order to gain access to public places or other locations.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that paperbased vaccination certificates were generally favoured over digital COVID-19 vaccination certificates [10]. In addition, benefits of digital COVID-19 vaccination certificates and paper-based COVID-19 vaccination certificates should not be limited to documentation purposes only, as cited in [10]. Digital COVID-19 vaccination certificates can be used to execute various functions.…”
Section: The Format Covid-19 Vaccination Certificate Must Takementioning
confidence: 99%
“…Digital and paper-based vaccine certificates were used for documentation purposes only [assumed]. The results showed that paperbased vaccination certificates were generally favoured over digital COVID-19 vaccination certificates [10]. In addition, benefits of digital COVID-19 vaccination certificates and paper-based COVID-19 vaccination certificates should not be limited to documentation purposes only, as cited in [10].…”
Section: The Format Covid-19 Vaccination Certificate Must Takementioning
confidence: 99%
See 2 more Smart Citations